A criminological study of educators’ perceptions regarding learner-to-learner school violence in rural communities of Limpopo province - Mothibi, Kholofelo A. (Acta criminologica, 2017)
This study explored teachers’ perceptions regarding the factors that influence learner-tolearner school violence in the rural area of Mokomene village, Molemole Municipality in Capricorn District, Limpopo Province, South Africa. The major objectives of this article were, namely: i) to understand the nature of bullying; ii) to establish the factors contributing to bullying; and iii) to discover the impact of learner-on-learner bullying and violence at the school premises. Eight educators from one school were constituted as a sample of this study utilising a qualitative, exploratory, descriptive and contextual design. The findings of this study highlighted the nature and various causes of bullying and violence which may help in the formulation and implementation of various strategies to reduce the bullying behaviour of learners in order to improve their learning. The study concludes that the safety of learners at school should be considered to reduce fear of victimisation among learners. This can be done through collaboration between community structures such as families, community members and school authorities, so as to reduce the persistence of violence at school premises as well as within the community.